IMPLEMENTASI UU NO 16 TAHUN 2017 TENTANG ORGANISASI KEMASYARAKATAN DI BADAN KESATUAN BANGSA DAN POLITIK KABUPATEN SUMEDANG - arip rahman sudrajat; Deni agustian; Hilal Mauludani; Indriyanti Afrilia; Muhamad Yunus; Siti Meilani (LPPM UNSAP & FISIP UNSAP, 2023)
Currently in every region there are more and more social organizations formed from various circles. Therefore, the existence of this research is so that people's insight and knowledge will increase because of the need for innovation and an attitude of cooperation to encourage and assist the course of community life and government programs if a good community empowerment organization is implemented. The purpose of this researcher is to find out the implementation of the policy of law number 16 of 2017 concerning social organizations by the national unitary and political unit of Sumedang district. The research method used is a qualitative method. The technique for determining the informants was to use a purposive sampling technique with informants consisting of: the secretary of the Sumedang district national and political agency, the head of national alertness and conflict management, the head of domestic politics and community organizations, the head of ideology of national insight and economic, social, cultural resilience, and religion, and the chairman of the mass organization. Data collection techniques used were library research and field studies consisting of observation, interviews, documentation and triangulation. While the data processing procedures are data reduction, data display, data conclusion drawing/verification. Based on the results of the study, it was concluded that it had been going quite well in implementing the policy, but there were inhibiting factors regarding the lack of supporting resources in carrying out socialization, and the lack of understanding of CSOs on the Law on CBOs. Obstacles were found regarding the implementation of this policy, namely: there are in terms of supporting resources, participation of mass organizations, and the absence of written sanctions for organizations that do not report. Efforts to overcome obstacles include increasing auxiliary resources, conducting socialization during organizational secretarial surveys, and applying social sanctions.